PENGARUH KEPRIBADIAN, KARAKTERISTIK PEKERJAAN TERHADAP KINERJA PEGAWAI DIMEDIASI KEPUASAN KERJA (Studi Pada Dinas Perhubungan, Komunikasi dan Informatika Kota / Kabupaten Tegal) - Hartoto, Hartoto (Students Journal of Economic and Management, 2012)
Performance is an important factor for employees and organization. Without a good employee performance then the organization will have difficulty in achieving its goals. To achieve good performance is affected by several factors. This research aimed to examine and analyze the influence of personality and job characteristics on the performance of the civil servants at the Department of Transportation, Communication and Information Tegal city and Tegal regency. Data collection was conducted through a questionnaire with a population of employees at the Department of Transportation, Communication and Information Tegal city and Tegal regency, while the method of sampling using purposive sampling with the number of respondents 131 people. Data analize through SPSS version 16 include validity, reliability test, coefficient of determination test, ANOVA test and hypothesis test.The results test showed that personality (big five personality) have a significant effect on job satisfaction, job characteristics a significant effect on job satisfaction, personality (big five personality) a significant effect on performance, job characteristics a significant effect on performance and job satisfaction a significant effect on performance. Mediation test results showed that job satisfaction does not mediate the effect of personality on the performance and Job satisfaction das not mediate the effect of job characteristics on performance . Keywords: Personality, Job Characteristics, Job Satisfaction and Performance